Uninformed partisans? The redistributive preferences of young Greeks - Koutsiaras, Nikos; Tsirbas, Yannis (The Greek Review of Social Research, 2021)
This paper adds to the literature on subjective redistributive preferences. Ιt aims at explaining the preferences of young people, a theme which has, paradoxically, been underresearched. The paper explores specific preferences over a range of redistributive policies and labour market institutions. A two-stage research strategy is employed to trace the impact of information, as well as the influence of self-interest, personal economic prospects, ideology, and political attitudes on redistributive preferences in a sample of 533 students. The provision of information – that is, lifting the porous veil of ignorance facing young persons – has virtually no effect on preferences. Two mechanisms are uncovered: an ideological-political and a political-economic one. The latter explains the intensity of redistributive preferences, but not their content and direction.